Mechanisms of Pathogenic Tau and Aβ Protein Spreading in Alzheimer’s Disease - d‘Errico, Paolo; Meyer-Luehmann, Melanie (Frontiers in Aging Neuroscience, 2020)
Alzheimer´s disease (AD) is pathologically defined by the presence of amyloid-β (Aβ) plaques, neurofibrillary tangles and neuronal loss. In general, the aggregation of Aβ is considered an essential trigger in AD pathogenesis that gives rise to neurofibrillary tangles, neuronal dysfunction and dementia. During the process leading to AD, tau and Aβ first misfold and form aggregates in one brain region, from where they spread to interconnected areas of the brain thereby inducing its gradual morphological and functional deterioration. In this mini-review, we present an overview of the current literature on the spreading mechanisms of Aβ and tau pathology in AD since a more profound understanding is necessary to design therapeutic approaches aimed at preventing or halting disease progression.